Acute toxicity and micronucleus test of conotoxin lt14a in mice. Issue 1 (28th March 2021) - Wu, Yun; Qiang, Yuanyuan; Zhang, Guangxian; Zhou, Maojun
Abstract: Conotoxins, which target ion channels or neurotransmitter receptors with high specificity, are valuable in drug development for pain, epilepsy and other neurological diseases. However, the toxicology of conotoxins is rarely reported. In this study, we primarily researched parts of the pharmacological and toxicological properties of an analgesic conotoxin lt14a. Three doses of lt14a (1, 5 and 10 mg/kg) could prolong the pentobarbital‐induced sleep time of mice and showed no significant effect on the spontaneous locomotor activity of mice. Three doses of lt14a (50, 100 and 200 mg/kg) did not increase micronucleus rate in the micronucleus test. In addition, three doses of lt14a (200, 500 and 1000 mg/kg) showed no pathological change on the heart or brain of mice in the acute toxicity test. The high dose of lt14a (1000 times the effective analgesic dose) had a certain damaging effect on the liver and lung according to serological detection and histopathology. As part of the preclinical studies, our results provide acute toxicity and mutagenicity evaluation of the promising analgesic conotoxin lt14a.